2003
DOI: 10.1002/uog.62
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and interobserver variability of ovarian volume, gray‐scale and color flow indices obtained using transvaginal three‐dimensional power Doppler ultrasonography

Abstract: Objective To assess intraobserver and interobserver variability in ovarian volume and gray-scale and color flow index measurements using transvaginal, threedimensional, power Doppler ultrasonography. Methods VI, 0.70 and 0.81, respectively), but for FI measurements the reproducibility was poor (inter-CC = 0.29, r = 7.87). Conclusions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 20 publications
2
61
1
10
Order By: Relevance
“…Raine-Fenning et al 6,7 also showed high intraobserver and interobserver reproducibility of ovarian 3D-PDA indices. The Intra-CC and, particularly, Inter-CC were not as high as those of Jarvela et al 5 These authors observed an FI Inter-CC of just 0.29 in 22 ovaries after 8 days with controlled stimulation treatment. We observed an FI Inter-CC of 0.898, just slightly lower than VI and VFI CCs.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Raine-Fenning et al 6,7 also showed high intraobserver and interobserver reproducibility of ovarian 3D-PDA indices. The Intra-CC and, particularly, Inter-CC were not as high as those of Jarvela et al 5 These authors observed an FI Inter-CC of just 0.29 in 22 ovaries after 8 days with controlled stimulation treatment. We observed an FI Inter-CC of 0.898, just slightly lower than VI and VFI CCs.…”
Section: Discussioncontrasting
confidence: 52%
“…In general, the mean ovarian volume is more reproducible after ovarian stimulation, whereas Doppler indices are more reproducible in the basal ovary after pituitary suppression. Jarvela et al 5 and Raine-Fenning et al 6,7 recently evaluated intraobserver and interobserver repeatability of the ovarian volume by the rotational method. In accordance with our findings, both groups observed excellent reproducibility, with Intra-CC and Inter-CC very close to 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the reproducibility of the whole procedure, that is, from the volume acquisition, was not tested. There are two ways of analyzing reliability involving the use of the threedimensional technique: by 3D volume acquisition and by volume calculation after definition of the contour by VOCAL method (17) . The reliability of three-dimensional volume acquisition is directly related to the level of confidence in accurately performing the contour definition on which the volume will be calaculated 18) .…”
Section: Discussionmentioning
confidence: 99%